Accelerators to eliminate hunger and malnutrition - Compact2025 (International Food Policy Research Institute, 2018)
Progress in eliminating hunger and malnutrition is too slow. Despite some periods of significant progress, reductions in hunger and undernutrition on a global scale have stagnated since 2000, and progress has varied widely across countries. In 2017, the number of undernourished people worldwide rose to nearly 821 million from around 804 million in 2016, and 151 million children remain stunted. At the same time, overweight, obesity, and associated noncommunicable diseases are rising faster than undernutrition is declining. Rapid urbanization, climate change, and continued conflict pose further threats to our global food system. If the world is to end hunger and malnutrition by 2030—the target year to achieve the Sustainable Development Goals (SDGs)—it is time to pick up the pace.